Helicobacter pylori-Epithelial Cell Interactions: From Adhesion to Apoptosis - Nicola L Jones; Philip M Sherman (Canadian Journal of Gastroenterology)
Studies suggest that host cell signal transduction cascades are manipulated during infection with microbes, including the gastric pathogen Helicobacter pylori. Several putative adhesins have been proposed to mediate the attachment of H pylori to gastric epithelial cells. Following bacterial binding, a series of signalling pathways are activated in the infected gastric epithelial cell. These signals include both cytoplasmic (such as vacuolization, tyrosine phosphorylation and elevation of cytosolic calcium) and nuclear (proliferation, apoptosis and chemokine transcription) events. Research aimed at elucidating the interactions that occur between the host cell and the bacterium during infection should improve the limited knowledge of disease pathogenesis.